Cancelable Fingerprint Features Using Chaff Points Encapsulation (Informatica, 2018)
Recently, Biometrics imaging is widely used in several security areas such as security monitoring, database access, border control and immigration, and for reliable personal verification, identification and recognition schemes. To determine or confirm the identity of an individual's based on their physiological and/or behavioral characteristics, biometric features must be used. The aim of this paper is to review cancelable biometric generation and protection schemes. An approach for generating chaff points for fingerprint template features encapsulation as fingerprint cancelability infrastructure has been presented. Results show that strong positive correlation of original minutiae scores go with high decapsulated minutiae scores. To test the given cancelable approach performance two indexes are used, FAR (false accept rate) and FRR (false reject rate).